Third-wave feminism reflected in the American television series “Charmed” = Nữ quyền làn sóng thứ ba thể hiện trong phim truyền hình Mỹ “Phép thuật” - Đỗ, Thị Trang (2021)
Feminism arises as a social phenomenon that helps women achieve gender equality with more rights and freedom. The US has witnessed the rise of feminism through three waves in which the first and second waves paved the way for the third wave to empower women with more rights and freedom. To understand more about third-wave feminism in the American contemporary society, the researcher conducted a qualitative study on the reflection of third-wave feminism characteristics in one popular television series spanning from 1998 to 2006, Charmed. Adopting the observation data collection method and the content analysis method, the researcher studied the pro-choice and pro-sex characteristics of third-wave feminism in Charmed and found that pro-choice includes the choice of identity, career, rules, love and marriage; pro-sex includes sex as an indispensable part of life and sex as a means, not an end in itself. Overall, levels of pro-sex and pro-choice are manifested in four main characters but a particular sub-characteristic can be seen more clearly and regularly in one character than the others. In this sense, diversity is the essence of third-wave feminism in which each woman reflects its characteristics differently.